1977
DOI: 10.1021/ed054p376
|View full text |Cite
|
Sign up to set email alerts
|

Identification of FD&C dyes by visible spectroscopy. A consumer-oriented undergraduate experiment

Abstract: Absorption maxima and procedures for identifying 11 FD&C dyes through visible spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1978
1978
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 1 publication
1
11
0
Order By: Relevance
“…Yellow #6 was chosen as a marker compound to determine encapsulation efficiency of an active in the inner aqueous phase and release properties of W/O/W emulsions. Through full scanning from 200 – 700 nm using spectrophotometry (Spectronic 20, Spectronic Instrument, Inc., Rochester, NY, USA), the maximum absorbance of yellow #6 was found to be 480 nm, which agrees with the literature . A standard curve for determining the migration of yellow #6 from the inner phase to the bulk continuous phase was developed by measuring the absorbance of a serial dilution of yellow #6 solutions (absorbance of all solutions was within the readable range of the spectrometer i.e., 0.2 – 0.8 absorbance units).…”
Section: Methodsmentioning
confidence: 78%
“…Yellow #6 was chosen as a marker compound to determine encapsulation efficiency of an active in the inner aqueous phase and release properties of W/O/W emulsions. Through full scanning from 200 – 700 nm using spectrophotometry (Spectronic 20, Spectronic Instrument, Inc., Rochester, NY, USA), the maximum absorbance of yellow #6 was found to be 480 nm, which agrees with the literature . A standard curve for determining the migration of yellow #6 from the inner phase to the bulk continuous phase was developed by measuring the absorbance of a serial dilution of yellow #6 solutions (absorbance of all solutions was within the readable range of the spectrometer i.e., 0.2 – 0.8 absorbance units).…”
Section: Methodsmentioning
confidence: 78%
“…Extension and modification of these experiments can easily be worked out. For example, it should be possible to determine quantitatively the amount of dye that is adsorbed on the egg by visible spectroscopy (19).…”
Section: Discussionmentioning
confidence: 99%
“…These colors may then be analyzed by liquid chromatography under slightly different conditions. 5 k' can be defined as the difference between the time necessary for solvent molecules (or other non-retained compounds) to travel the length of the column (to) and the time required for the component to traverse the column (ti) divided by to. (See Figure 2).…”
Section: Instrumentationmentioning
confidence: 99%
“…Artificial colors were chosen for study because of demonstrated student interest resulting from the continuing controversy over additive safety. Furthermore, this experiment can be used in conjunction with previously reported tic and spectroscopic studies of food colors (4,5).…”
mentioning
confidence: 95%